TINJAUAN AKUNTABILITAS DAN TRANSPARANSI LAPORAN KEUANGAN LAZISMU KOTA KISARAN BERDASARKAN PERSPEKTIF PSAK 109 - Hidayat, Syahrijal (Universitas Dharmawangsa, 2025)
Lembaga Amil Zakat, Infaq dan Shadaqah Muhammadiyah (Lazismu) as a zakat management organization has significant responsibility in achieving accountability and transparency in financial reporting to stakeholders. This study aims to analyze the level of accountability and transparency of Lazismu Kisaran City's financial reports based on PSAK 109 provisions regarding Zakat and Infaq/Shadaqah Accounting. This research employs a descriptive qualitative method with a case study approach. Primary data was obtained through in-depth interviews with administrators and financial managers of Lazismu, while secondary data included financial reports for the period 2021-2023, standard operating procedures, and related regulations. Data analysis techniques used the Miles and Huberman model with source triangulation to validate findings. The results indicate that Lazismu Kisaran City has implemented most PSAK 109 provisions in financial report preparation, although some aspects have not fully complied with the standards, such as disclosure of zakat distribution policies and presentation of fund change reports. The organization's accountability level is in the good category with a score of 78%, characterized by periodic reporting mechanisms, internal audits, and adequate internal control systems. Meanwhile, financial reporting transparency achieved a score of 72%, where financial information has been regularly published through websites and social media, but still requires improvement in terms of accessibility and completeness of information for the general public. This research contributes theoretically to the development of public sector accounting literature, particularly religious-based nonprofit organizations, and provides practical recommendations for Lazismu to improve financial reporting quality in accordance with PSAK 109 to strengthen public trust and optimize community fund management.